2003
DOI: 10.1289/ehp.5862
|View full text |Cite
|
Sign up to set email alerts
|

The upper airway response to pollen is enhanced by exposure to combustion particulates: a pilot human experimental challenge study.

Abstract: Although human experimental studies have shown that gaseous pollutants enhance the inflammatory response to allergens, human data on whether combustion particulates enhance the inflammatory response to allergen are limited. Therefore, we conducted a human experimental study to investigate whether combustion particulates enhance the inflammatory response to aeroallergens. "Enhancement" refers to a greater-than-additive response when combustion particulates are delivered with allergen, compared with the response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…41 Other forms of air pollutant exposure include oil fly ash, a particulate produced from coal combustion. Hauser et al (2003) found increased nasal lavage leukocytes, neutrophils, and IL-4 in AR subjects coexposed to an allergen and residual oil fly ash. 42 Coexposure with allergen and atmospheric levels of ozone resulted in elevated nasal lavage neutrophils, eosinophils, and mononuclear cells.…”
Section: Recent Studies and Current Treatmentsmentioning
confidence: 84%
“…41 Other forms of air pollutant exposure include oil fly ash, a particulate produced from coal combustion. Hauser et al (2003) found increased nasal lavage leukocytes, neutrophils, and IL-4 in AR subjects coexposed to an allergen and residual oil fly ash. 42 Coexposure with allergen and atmospheric levels of ozone resulted in elevated nasal lavage neutrophils, eosinophils, and mononuclear cells.…”
Section: Recent Studies and Current Treatmentsmentioning
confidence: 84%
“…Previous studies on human subjects have reported that nasal exposure to ozone (64) or particulate matter air pollution (65) followed by challenge with allergen significantly enhanced the allergic responses. Similarly, repeated pollen exposure amplified and sustained allergic symptoms (66).…”
Section: Discussionmentioning
confidence: 99%
“…A potent and largely overlooked factor is the rapid transformation of natural vegetation via a grass-fire cycle. The ongoing broadscale use of fires in tropical regions (van der Werf et al, 2006;Turner et al, 2007) produces severe recurrent episodes of particulate air pollution, which can further potentiate the clinical response to allergen exposure (Hauser et al, 2003;Saxon and Diaz-Sanchez, 2005). It might also be possible that tropical grasses with the C4 photosynthetic pathway are more allergenic than temperate grasses, explaining the strong association we observed with very low concentrations of grass pollen.…”
Section: Discussionmentioning
confidence: 99%